Evaluation of immune responses induced by rhoptry protein 5 and rhoptry protein 7 DNA vaccines against Toxoplasma gondii. (April 2016) - Wang, L.; Lu, G.; Zhou, A.; Han, Y.; Guo, J.; Zhou, H.; Cong, H.; He, S.
Summary: Infection with the protozoan parasite Toxoplasma gondii is widespread, and the organism can cause congenital infections in humans. The horizontal transmission of Toxoplasma is even more common than congenital. An effective vaccine strategy brings the prospect of improving Toxoplasma disease control. Rhoptry protein 5 (ROP5) and ROP7 are potential stimulators of humoral and cellular immune responses. In this study, we constructed a multi‐antigenic DNA vaccine expressing ROP5 and ROP7 of T. gondii and compared the protective efficacy to single‐gene vaccines and control groups. BALB/c mice were immunized intramuscularly three times. The levels of IgG antibodies and cytokines in mice immunized with the multi‐antigenic DNA vaccine (pROP5/ROP7) were significantly higher than those in the control mice. Mice vaccinated with pROP5/ROP7 showed a longer survival time (16 days) than single‐gene‐immunized mice (11 and 12 days, respectively) or control mice (8 days) after a challenge with 1 × 10 4 tachyzoites of RH strain of T.  gondii. Furthermore, after intragastric infection with 20 cysts of PRU strain of T. gondii, the number of brain cysts in mice immunized with pROP5/ROP7 was only 25% of the number in control mice. Our results showed that a DNA vaccine encoding ROP5 and ROP7 significantly enhanced protection against T. gondii challenge.